2005
DOI: 10.1136/bjo.2004.044685
|View full text |Cite
|
Sign up to set email alerts
|

Elevated aqueous humour tissue inhibitor of matrix metalloproteinase-1 and connective tissue growth factor in pseudoexfoliation syndrome

Abstract: Background/aims: Pseudoexfoliation syndrome (PXF) was recently found to be associated with increased expression of transforming growth factor b 1 (TGFb 1 ) in the aqueous humour. As concern has been raised regarding anti-TGFb therapy, which can potentially disrupt the maintenance of anterior chamber associated immune deviation, the authors explored the levels of tissue inhibitor of matrix metalloproteinase-1 (TIMP-1), matrix metalloproteinase-9 (MMP-9), and connective tissue growth factor (CTGF) in aqueous hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1
7

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 52 publications
3
45
1
7
Order By: Relevance
“…Other regulated genes with calcification implications, such as CTGF, CALB2, STATH, OGN, and SPARC were also found and could be relevant for the trabecular meshwork. CTGF, which was generally altered by the elevated pressure, is elevated in the aqueous humor of patients with pseudoexfoliation glaucoma (32). Also regulated in most individuals were CALB2, a vitamin D-dependent calcium-binding protein involved in calcium homeostasis and mineralization (25,38), and SPARC, a calcium and collagen binding protein recently proposed to be a collagen chaperone (44).…”
Section: Discussionmentioning
confidence: 99%
“…Other regulated genes with calcification implications, such as CTGF, CALB2, STATH, OGN, and SPARC were also found and could be relevant for the trabecular meshwork. CTGF, which was generally altered by the elevated pressure, is elevated in the aqueous humor of patients with pseudoexfoliation glaucoma (32). Also regulated in most individuals were CALB2, a vitamin D-dependent calcium-binding protein involved in calcium homeostasis and mineralization (25,38), and SPARC, a calcium and collagen binding protein recently proposed to be a collagen chaperone (44).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the CTGF levels in AqH of patients with PXFG were significantly higher than in POAG and normal control subjects. 37,38 Therefore, we examined the fibrotic potential of AqH samples from PXFG and POAG patients using nonglaucomatous cataract samples as controls. Exposure of TM and LC cells to AqH from both PXFG and POAG patients significantly increased expression of profibrotic genes.…”
Section: Discussionmentioning
confidence: 99%
“…37 Pseudoexfoliation and primary open angle glaucoma patients were defined as previously described. 37 Sixteen cataract patients (73.8 6 9.7 years), 14 POAG patients (72.3 6 7.4 years), and 17 PXFG (80.7 6 7.2 years) were recruited and all were age-and sex-matched (P ‡ 0.05). Two to three AqH samples were pooled per experiment, depending on the original sample volume (50-100 lL per patient).…”
Section: Aqueous Humor Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…104 Given its profibrotic tendencies, it became a protein of interest in surgical models, demonstrating increased expression following glaucoma filtration surgery in rabbits and being associated with an elevated risk of bleb failure. 105,106 The putative role of CTGF in human glaucoma pathophysiology was first identified in pseudoexfoliation syndrome, 107,108 and attention soon focused on how CTGF regulates TM matrix deposition, 109,110 cellular tone, 111 and aqueous outflow facility. 112,113 In one promising recent study, the prostaglandin analog fluprostenol was found to mitigate CTGF-induced fibrogenesis in cultured human TM cells.…”
mentioning
confidence: 99%